Resistir e consolidar: um estudo sobre o Bacharelado em Ciências do Estado da Faculdade de Direito da Universidade Federal de Minas Gerais - Joao Protasio Farias Domingues de Vargas (2017)
This dissertation is a master's thesis of the Post-Graduate Program in Law, Faculty of Law of the Federal University of Minas Gerais, Brazil, in the research line State, Reason and History, collective project Macrophilosophy, Law and State, under the orientation of Prof. Dr. José Luiz Borges Horta, entitled Resit and Consolidate: a Study on the Bachelor of State Sciences of the Faculty of Law of the Federal University of Minas Gerais. The development includes aspects related to the State and State Sciences, the brazilian federal public universities development program (REUNI), the contribution of UFMG and the Faculty of Law, the three emerging Political-Pedagogical Projects in the genesis of the Course (Original, Alternative and Consolidated), under the Direction of Prof. Dr. Joaquim Carlos Salgado, between 2008 and 2010. The text discusses the various proposals of pedagogical policy and curricular matrix, with the cast and disciplinary arrangement; debate the identity of the Course between science and professionalization, as well as the monographic scientific production; focuses on the curricular reform of 2014-2016, the creation projects of the Department of State Sciences and Post-Graduation lato et stricto sensu. The conclusion shows that the brazilian State and contemporary created the State Sciences Course in search of itself within the process of globalizing expansion in the 21st century, making it as a kind of mirror of the State. A set of annexes presents original tables of the various curricula, the teachers' board, the student intellectual production, the teachers and evaluators, as well as a detailed data collection of all the course completion works defended between 2013 and 2016.